Transition metal-catalyzed radical functionalization of alkenes with alcohols and formamide derivatives - Cheng, Jun Kee (2016)
This thesis describes the transition metal-catalyzed radical functionalization of alkene with alcohols and formamides. A copper- or cobalt-catalyzed reaction protocol wherein the 1,3-enynes and arylalkenes underwent three-component oxyalkylation reaction with alcohols and hydroperoxides has been established. Direct α-C(sp3)-H activation of alcohol was achieved to assemble 1,3-dioxygenated molecular framework. Downstream chemical transformation allowed the β-peroxy alcohol product to give facile entry towards β-hydroxyynone and propargylic 1,3-diol. Building on this work, the reaction has been extended to employing formamide derivatives as the sources of aminocarbonyl moieties for oxycarbonylation reaction of alkenes via direct formyl C-H functionalization of formamides. The β-peroxy amide product could be subjected to chemical manipulation to afford the respective β-hydroxy amide, β-keto amide and β–lactam in follow-up reactions. In addition to the difunctionalization reaction, oxidative coupling of formamides and enamides was also successfully realized for the assembly of N-acyl enamine amides. The densely-functionalized amide products allowed efficient syntheses of pyrimidin-4-ones and 4-hydroxy-2-pyridinones.